PERHITUNGAN DAN PERANCANGAN IGNITER BERBASIS KALKULASI PROPULSI ROKET (Studi Kasus Roket RX-320) - Samosir, Ganda (BRIN Publishing, 2011)
The solid rocket motors, like all the LAPAN’s rocket, has been using the composite fuel of Hydroxyl Terminated Poly Butadiene (HTPB) type which is not easy to self-igniting. The quite extreme environment conditions are needed in order to ignite this non-hypergolic solid fuel, such as the ambiance pressure and temperature must be about 40 bar and 280°C respectively. The aforementioned conditions must be well given by the prime igniter designed or commonly known as igniter. The performance of an igniter could be very influenced by 2 (two) massive variables; first one is the internal factor, such as: squib ingredient, filament material, primer composition, igniter main charge, and the second one is external factor, such as: propellant’s type, dimension and the configuration of the rocket’s combustion chamber. In other word, chosen the proper rocket’s igniter are depending on the type and its mission.The propulsion calculation applied in this paper to design the igniter of the rocket RX-320, gives some major variables, i.e.: the biggest tube length; = 357 mm, its outside diameter; = 51 mm, total orifices and its diameter are 165 and 4 mm respectively.